Universal Combustion Chamber for Utilization of Petroleum Gases of Different Composition and Heat Output - Shilova A.A.; Bachev N.L.; Matyunin O.O. (Problems of the Regional Energetics)
When developing micro-gas turbine power plants, it is necessary to have universal two-zone combustion chambers for utilizing petroleum gases of different composition and heat output at different oil deposits. In the combustion zone, the excess air ratio is selected from the interval between the lower and upper concentration limits of combustion. In the dilution zone by supply-ing secondary air, the working fluid with specified parameters is prepared for supply to the tur-bine. The excess air coefficient at the exit from the combustion chamber is determined from the energy balance equation and depends on the air and fuel gas parameters at the entrance to the combustion chamber and on the temperature of the working fluid at the entrance to the turbine. The purpose of this work is to develop recommendations for creating a universal combustion chamber for combustion of fuel gases of different composition and heat output. This goal is achieved by selecting the diameter of the chamber in order to ensure the required ratios between the average flow rate of the combustible air mixture and the rate of turbulent combustion, at which a stable position of the flame front is observed. The most noticeable result of the research conducted is substantiation of the possibility of using a universal combustion chamber with con-stant dimensions in utilization gas turbine installations designed for burning non-standard fuel gases with ballasting components content up to 70%, which will reduce the time and cost of de-velopment and implementation of these installations.